Childhood Hypertension and Effects on Cognitive Functions: Mechanisms and Future Perspectives - Tyner, Emma; Oropeza, Marie; Figueroa, Johnny; Peña, Ike C. dela (CNS & Neurological Disorders - Drug Targets, 2019)
Pediatric hypertension is currently one of the most common health concerns in children, given its effects not only on cardiovascular but also cognitive functions. There is accumulating evidence suggesting neurocognitive dysfunction in hypertensive children that could persist even into adulthood. Identifying the precise mechanism(s) underlying the association between childhood hypertension and cognitive dysfunction is crucial as it could potentially lead to the discovery of “druggable” biological targets facilitating the development of treatments. Here, we discuss some of the proposed pathophysiological mechanisms underlying childhood hypertension and cognitive deficits and suggest strategies to address some of the current challenges in the field. The various research studies involving hypertensive adults indicate that long-term hypertension may produce abnormal cerebrovascular reactivity, chronic inflammation, autonomic dysfunction, or hyperinsulinemia and hypercholesterolemia, which could lead to alterations in the brain’s structure and functions, resulting in cognitive dysfunction. In light of the current literature, we propose that dysregulation of the hypothalamus-pituitaryadrenal axis, modifications in endothelial brain-derived neurotrophic factor and the gut microbiome may also modulate cognitive functions in hypertensive individuals. Moreover, the above-mentioned pathological states may further intensify the detrimental effects of hypertension on cognitive functions. Thus, treatments that target not only hypertension but also its downstream effects may prove useful in ameliorating hypertension-induced cognitive deficits. Much remains to be clarified about the mechanisms and treatments of hypertension-induced cognitive outcomes in pediatric populations. Addressing the knowledge gaps in this field entails conducting not only clinical research but also rigorous basic and translational studies.
Keywords: cognitive dysfunction